First-aid treatment of epistaxis–confirmation of widespread ignorance. Issue 868 (February 1998) - Strachan, D.; England, J.
Abstract : A survey of 500 members of the public was carried out in which they were asked how they would deal with a nose bleed. Only 50 out of 443 responses were judged as being correct, confirming a clinical impression, long held by those dealing with epistaxis, that there is a high level of ignorance as to the correct first aid treatment. The survey also suggested that the lack of knowledge was not confined to the general public but evident in those trained in healthcare.